1999
DOI: 10.1557/jmr.1999.0497
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of initial stage of Ni thin-film growth on a TiO2 (110) surface

Abstract: The bonding structure and binding character for the initial stage of thin-film growth of Ni on a rutile (110) surface were studied using first-principles density functional theory. Our results show that, in the first monolayer, Ni atoms are preferentially adsorbed on top of bridging oxygen atoms and upon secondary surface oxygen. The bond strength between Ni adatom and substrate is much stronger than that between Ni adatoms. About 0.3 electrons are transferred from Ni atoms to substrate in low coverage; the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…[17,23 -25] However, there is disagreement on the charge transfer direction. [20 -22] In Refs [21] and [22] , it was reported that 0.10 ∼ 0.30 electrons per Ni atom were transferred from Ni to TiO 2 , while ∼0.10 electrons per Ni atom were found to be transferred from TiO 2 to Ni in Ref. [20] .…”
Section: Resultsmentioning
confidence: 99%
“…[17,23 -25] However, there is disagreement on the charge transfer direction. [20 -22] In Refs [21] and [22] , it was reported that 0.10 ∼ 0.30 electrons per Ni atom were transferred from Ni to TiO 2 , while ∼0.10 electrons per Ni atom were found to be transferred from TiO 2 to Ni in Ref. [20] .…”
Section: Resultsmentioning
confidence: 99%
“…10(D)), which can be assigned to lattice oxygen O 2− , bridging OH, terminal OH and adsorbed H 2 O, respectively [35]. The OH attributes greatly to the sorption of Eu(III) on TiO 2 surface.…”
Section: Xps Analysismentioning
confidence: 99%
“…According to a theoretical calculation, the atop site of bridging oxygen atoms might be the most stable site on the terrace [3]. However, the single Ni-bridging oxygen bond is not sufficiently strong to fix it on the atop site.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical investigations have examined single atoms of Group 10 elements deposited on the TiO2 (110) surface. Most of those studies have indicated that the metal interacts mainly with oxygen, especially bridging oxygen atoms [3][4][5][6]. On the other hand, experiments on metal clusters and TiO2(110) such as XPS and STM have suggested that the metal preferably interacted with the five-fold Ti sites [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%